KEMANDIRIAN PANGAN KELOMPOK NELAYAN MELALUI PENERAPAN IMTA (INTEGRATED MULTI TROPHIC AQUAQULTURE) DI KARAMBA TANCAP DESA BOKORI, KONAWE SULAWESI TENGGARA - Asriyana, Asriyana; Yusnaini, Yusnaini; Cayah, Nur; Ishak, Ermayanti (Jurnal Abdi Insani, 2025)
Food self-sufficiency among coastal communities is an essential aspect in achieving sustainable food security. Bokori Village in Konawe Regency has significant potential for aquaculture development; however, current practices that rely on monoculture still create challenges, such as the accumulation of organic waste, declining water quality, and high vulnerability of cultured organisms to diseases. To address these issues, a multiculture approach known as Integrated Multi Trophic Aquaculture (IMTA) was applied in fixed-net cages (karamba tancap) as an innovative and environmentally friendly solution. This community engagement program aimed to enhance food self-sufficiency of fisher groups through the diversification of aquaculture products while maintaining aquatic ecosystem quality. The activities were carried out using a participatory approach involving two fisher groups, Usaha Bersama and Langkoe, whose main livelihoods include fishing, fish trading, and fish processing. The program stages consisted of socialization of the IMTA concept, construction of IMTA-based fixed-net cages, stocking of fish seeds and extractive organisms (seaweed, abalone, and sea cucumber), and technical assistance in maintenance. Evaluation was conducted through monitoring of water quality, survival rates of cultured organisms, as well as improvements in fishers’ knowledge and skills. The results showed that the IMTA system effectively utilized organic waste from fish culture as nutrients for extractive organisms, thus maintaining relatively stable water quality. Fisher groups achieved higher productivity through diversified harvests that included not only fish but also seaweed and other high-value species. Moreover, fishers demonstrated increased understanding of sustainable and integrated aquaculture practices. The application of IMTA in fixed-net cages in Bokori Village has proven to support food self-sufficiency of fisher groups, improve community welfare, and contribute significantly to the development of sustainable aquaculture systems in coastal areas.